Implementasi Kebijakan Pengelolaan Pajak Air Tanah Pada Peraturan Daerah Kabupaten Badung Nomor 1 Tahun 2011 - Widhianti, Kadek Wiga; Supriliyani, Ni Wayan; Purnamaningsih, Putu Eka (CITIZEN CHARTER, 2018)
ABSTRACT The policy of managing groundwater tax in Badung Regency is in accordance with the Badung Regency Regional Regulation Number 1 of 2011 concerning on groundwater tax where this regulation have a functions as an instrument to implementing supervision, control and environmental conservation in the utilization of ground water so that the availability of water is maintained and fulfilled in accordance with its utilization. Therefore, this research aims to find out how the implementation of groundwater tax management policy in the Badung Regency Regional Regulation Number 1 of 2011, this research used descriptive qualitative methods. The results showed that the performance of groundwater tax management policy in Badung Regency was not optimal because the standards set were still unclear, communication was not effective, the taxpayers were less cooperative and the attitude of the implementers and the application of less strict sanctions. Keywords: Implementation, Tax, Groundwater